BASIC IMMUNIZATION STATUS CORRELATED TO MORBIDITY AND MORTALITY OF SEVERE PNEUMONIA IN TODDLERS - Eddy Teguh Pribadi; Sri Martuti; Nugroho, Hari Wahyu (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Pneumonia is an acute lung infection that often affects toddlers and is a major cause of morbidity and mortality. Routine immunization is an important preventive measure. This study aims to analyze the relationship between immunization status and morbidity and mortality of toddlers with severe pneumonia in the PICU of Dr. Moewardi Regional Hospital. The retrospective cross-sectional analytical study design used medical record data and the Menuju Sehat Card in 34 toddlers. Immunization status was considered complete if appropriate for age. Morbidity was seen from the length of hospitalization, mortality from the status of alive/dead. Analysis used chi-square/Fisher and logistic regression. The results showed that 90% of toddlers with complete immunization were hospitalized for <10 days, while 82.6% with incomplete immunization were hospitalized for ≥10 days (p<0.001). Mortality was higher with incomplete immunization (90.0%) than with complete immunization (45.8%) (p=0.024). DPT3 and smallpox immunization were associated with morbidity, while polio and smallpox were associated with mortality. Conclusion: Basic immunization is an independent predictor of morbidity and mortality in severe pneumonia in toddlers after controlling for age, exclusive breastfeeding, and cigarette smoke exposure.